Effect of microstructures on dielectric breakdown strength of sintered reaction‐bonded silicon nitride ceramics. Issue 2 (20th October 2022) - Nakashima, Yuki; Zhou, You; Tanabe, Keisuke; Arima, Souhei; Hirao, Kiyoshi; Ohji, Tatsuki; Murayama, Norimitsu; Fukushima, Manabu
Abstract: Silicon nitride (Si3 N4 ) was prepared from silicon by a sintered reaction‐bonded silicon nitride method using yttria and magnesia as sintering additives. Post‐sintering (PS) of nitrided compacts was carried out at 1850°C under a nitrogen pressure of 1 MPa. Effect of PS time on microstructure and dielectric breakdown strength (DBS) of the prepared Si3 N4 ceramics was evaluated. The DBS was measured using specimens with four different thicknesses (0.30, 0.20, 0.10, and 0.05 mm) in order to examine the thickness dependence. The porosity of the sintered Si3 N4 decreased by prolonging the PS time, and the full density could be achieved at the PS time of over 6 h. After full densification, rod‐like β‐Si3 N4 grains grew up, and their maximum grain size increased from 45.1 to 154.7 μm by prolonging the PS time from 6 to 48 h. The DBS of the thick Si3 N4 substrates (0.30 mm) showed little variation from 35.4 to 47.0 kV/mm, regardless of the PS time. On the other hand, that of the thin ones (0.05 mm) dramatically decreased from 99.5 to 9.8 kV/mm with increased the PS time from 6 to 48 h. Because the DBS sharply decreased at the thin substrate sintered for longer time in which some large‐elongated grains might span the substrate thickness‐wise throughout, it was inferred that the interface between β‐Si3 N4 grains and grain boundary phase/intergranular glassy films might be a path of the dielectric breakdown.